Mining inorganic environment-friendly reinforcing material and application thereof

Through the hydration reaction technology of inorganic environmentally friendly reinforcement materials, the problem of coal combustion caused by high reaction temperature of polymer organic reinforcement materials is solved, and the effects of low reaction heat, high flame retardant level and high construction efficiency are achieved.

CN119430848APending Publication Date: 2025-02-14SHANXI YUBANG NEW POWER SCI & TECH
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411577990.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

During the coal mining process of existing mines, the reaction temperature of polymer organic reinforcement materials is too high during use, which can easily cause coal combustion and insufficient construction efficiency and safety.

Method used

Provided is an inorganic environmentally friendly reinforcement material for mining, including components A, components B and components C. It can generate low-reaction heat hydrated calcium silicate and other products through hydration reaction, thereby enhancing the strength and stability of the material.

Benefits of technology

It has achieved the advantages of low reaction heat, high flame retardant level, high construction efficiency, safety and environmental protection, and can cure quickly to meet the needs of "taken after finishing".

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005122295630000061
    Figure BDA0005122295630000061
  • Figure BDA0005122295630000071
    Figure BDA0005122295630000071
  • Figure BDA0005122295630000081
    Figure BDA0005122295630000081
Patent Text Reader

Abstract

The invention provides a mining inorganic environment-friendly reinforcing material and application thereof, and belongs to the technical field of mining reinforcing materials. A component A comprises the following components in parts by mass: 60-80 parts of anhydrite, 5-20 parts of lime, 5-10 parts of silica fume, 2-8 parts of sodium silicate, 1-0.5 part of a naphthalene water reducer, 3-7 parts of an early strength agent and 0.2-0.8 part of lithium salt; the component B comprises the following components in parts by mass: 50-70 parts of cement clinker, 10-30 parts of slag cement, 5-10 parts of iron powder, 1-8 parts of aluminum sulfate, 5-10 parts of calcium carbonate and 0.5-1 part of sodium tripolyphosphate; the component C is prepared from the following components in parts by mass: 10 to 25 parts of water glass, 10 to 20 parts of emulsion, 40 to 60 parts of water, 5 to 10 parts of high-efficiency water reducing agent and 1 to 5 parts of triethanolamine. The mining inorganic environment-friendly reinforcing material provided by the invention is low in reaction heat and is not easy to cause coal combustion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mining reinforcement materials, and in particular to an inorganic environmentally friendly mining reinforcement material and application thereof. Background Art

[0002] At present, in the process of coal mining in underground coal mines, geological structures such as collapse columns, faults, and goafs are encountered, which lead to the inability to produce normally. Grouting reinforcement technology has become a popular method of governance to treat geological structures. Traditional technology uses cement grouting materials, which have certain disadvantages. Due to the low early strength of cement, it takes several days to wait for mining after grouting, which affects the efficiency of coal mining and has been abandoned. At present, new polymer grouting materials are widely used, including polyurethane, phenolic and polyurea polymer organic reinforcement materials. Such materials have high solidification efficiency and can achieve satisfactory physical strength in a short time. They do not affect the normal mining of coal mines underground, and are favored by the mine. However, since they are polymer organic substances, they have the following disadvantages during use: the reaction temperature is too high, which easily causes coal combustion. Summary of the invention

[0003] In view of this, the object of the present invention is to provide an inorganic environmentally friendly reinforcement material for mining and its application. The inorganic environmentally friendly reinforcement material for mining provided by the present invention has low reaction heat and is not easy to cause coal combustion.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides an inorganic environmentally friendly reinforcement material for mining, comprising independently packaged component A, component B and component C:

[0006] The component A comprises the following components by weight: 60-80 parts of anhydrous gypsum, 5-20 parts of lime, 5-10 parts of silica fume, 2-8 parts of sodium silicate, 0.5-1 parts of naphthalene-based water reducer, 3-7 parts of early strength agent, and 0.2-0.8 parts of lithium salt;

[0007] The B component includes the following components in parts by weight: 50-70 parts of cement clinker, 10-30 parts of slag cement, 5-10 parts of iron powder, 1-8 parts of aluminum sulfate, 5-10 parts of calcium carbonate, and 0.5-1 part of sodium tripolyphosphate;

[0008] The C component includes the following components in parts by weight: 10 to 25 parts of water glass, 10 to 20 parts of emulsion, 40 to 60 parts of water, 5 to 10 parts of high-efficiency water reducing agent, and 1 to 5 parts of triethanolamine;

[0009] The mass ratio of component A, component B and component C is 1:1:0.9-1.

[0010] Preferably, the component A comprises the following components in parts by mass: 60 parts of anhydrous gypsum, 20 parts of lime, 10 parts of silica fume, 2 parts of sodium silicate, 0.5 parts of naphthalene-based water reducer, 7 parts of early strength agent, and 0.5 parts of lithium salt;

[0011] The B component includes the following components by mass: 70 parts of cement clinker, 10 parts of slag cement, 10 parts of iron powder, 3 parts of aluminum sulfate, 7 parts of calcium carbonate, and 0.5 parts of sodium tripolyphosphate;

[0012] The C component includes the following components in parts by mass: 25 parts of water glass, 10 parts of emulsion, 50 parts of water, 10 parts of high-efficiency water reducing agent, and 5 parts of triethanolamine.

[0013] Preferably, the component A comprises the following components in parts by mass: 80 parts of anhydrous gypsum, 5 parts of lime, 5 parts of silica fume, 5 parts of sodium silicate, 0.7 parts of naphthalene-based water reducer, 4 parts of early strength agent, and 0.3 parts of lithium salt;

[0014] The B component includes the following components by weight: 50 parts of cement clinker, 30 parts of slag cement, 5 parts of iron powder, 4 parts of aluminum sulfate, 10 parts of calcium carbonate, and 1 part of sodium tripolyphosphate;

[0015] The component C comprises the following components in parts by mass: 15 parts of water glass, 20 parts of emulsion, 56 parts of water, 8 parts of high-efficiency water reducing agent, and 1 part of triethanolamine.

[0016] Preferably, the component A comprises the following components in parts by mass: 70 parts of anhydrous gypsum, 10 parts of lime, 7 parts of silica fume, 8 parts of sodium silicate, 1 part of naphthalene-based water reducer, 3.2 parts of early strength agent, and 0.8 parts of lithium salt;

[0017] The B component includes the following components by mass: 60 parts of cement clinker, 20 parts of slag cement, 7 parts of iron powder, 8 parts of aluminum sulfate, 5 parts of calcium carbonate, and 0.8 parts of sodium tripolyphosphate;

[0018] The component C comprises the following components in parts by mass: 10 parts of water glass, 20 parts of emulsion, 60 parts of water, 5 parts of high-efficiency water reducing agent, and 5 parts of triethanolamine.

[0019] Preferably, the particle size of the sodium silicate is 20-48 μm.

[0020] Preferably, the particle size of the calcium carbonate is 18 to 44 μm.

[0021] Preferably, the emulsion includes one or more of styrene-acrylic emulsion, pure acrylic emulsion and water-based polyurethane emulsion.

[0022] Preferably, the modulus of the water glass is 2.6-3.3.

[0023] Preferably, the early strength agent includes one or more of calcium formate, calcium chloride and sodium sulfate.

[0024] The present invention also provides an application of the inorganic environmentally friendly reinforcement material for mining described in the above technical solution, comprising the following steps:

[0025] Mixing component A with part of component C to obtain a first mixed material;

[0026] Mixing component B with the remaining component C to obtain a second mixed material;

[0027] The first mixed material and the second mixed material are injected into the coal rock mass.

[0028] The invention provides an inorganic environment-friendly reinforcing material for mining, comprising independently packaged component A, component B and component C.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The polyurethane, phenolic, and polyurea polymer organic reinforcement materials currently used contain active groups such as cyanate and hydroxyl groups, which undergo polymerization reactions to form chemical bonds such as carbamates. The reaction process is fast and the heat release is high. The inorganic environmentally friendly reinforcement material for mining of the present invention includes components A, B, and C, wherein cement clinker and gypsum can undergo hydration reactions when used to generate products such as hydrated calcium silicate, hydrated calcium sulfoaluminate, calcium hydroxide, and hydrated calcium aluminate. These products gradually harden, fill the pores of the material, and enhance the strength and stability of the material. The inorganic environmentally friendly reinforcement material for mining of the present invention is exothermic caused by hydration reaction, has low reaction heat, high flame retardant grade (A-grade non-combustible), safe to use (no harm to the human body, not easy to cause allergies, etc.), low reaction temperature, and not easy to cause coal combustion. The price is low. Since the coal is cut after the grouting is completed, the inorganic environmentally friendly mining reinforcement material will not adhere to the surface of the coal, which has the advantages of energy saving and emission reduction. Compared with the currently used cement grouting materials, the tricalcium aluminate and gypsum in the inorganic environmentally friendly mining reinforcement material of the present invention are hydrated quickly and release heat quickly to form hydrated calcium sulfoaluminate, which has the advantages of high construction efficiency, fast reaction speed and rapid solidification. The compressive strength is greater than 5MPa in 30 minutes, greater than 10MPa in 1 hour, and greater than 30MPa in 2 hours. After the grouting is completed, coal mining can be carried out. DETAILED DESCRIPTION

[0031] The present invention provides an inorganic environmentally friendly reinforcement material for mining, comprising independently packaged component A, component B and component C:

[0032] The component A comprises the following components by weight: 60-80 parts of anhydrous gypsum, 5-20 parts of lime, 5-10 parts of silica fume, 2-8 parts of sodium silicate, 0.5-1 parts of naphthalene-based water reducer, 3-7 parts of early strength agent, and 0.2-0.8 parts of lithium salt;

[0033] The B component includes the following components in parts by weight: 50-70 parts of cement clinker, 10-30 parts of slag cement, 5-10 parts of iron powder, 1-8 parts of aluminum sulfate, 5-10 parts of calcium carbonate, and 0.5-1 part of sodium tripolyphosphate;

[0034] The C component includes the following components in parts by weight: 10 to 25 parts of water glass, 10 to 20 parts of emulsion, 40 to 60 parts of water, 5 to 10 parts of high-efficiency water reducing agent, and 1 to 5 parts of triethanolamine;

[0035] The mass ratio of component A, component B and component C is 1:1:0.9-1.

[0036] In the present invention, unless otherwise specified, the raw materials used are all commercially available products in the art.

[0037] In the present invention, the particle size of the sodium silicate is preferably 20 to 48 μm, specifically 20, 34, 35 or 48 μm.

[0038] In the present invention, the particle size of the calcium carbonate is preferably 18 to 38 μm, specifically 18, 37 or 38 μm.

[0039] In the present invention, the emulsion preferably includes one or more of styrene-acrylic emulsion, pure acrylic emulsion and waterborne polyurethane emulsion. In the present invention, the solid content of the styrene-acrylic emulsion is preferably 40-50%, the solid content of the pure acrylic emulsion is preferably 35-45%, and the solid content of the waterborne polyurethane emulsion is preferably 20-35%.

[0040] In the present invention, the modulus of the water glass is preferably 2.6-3.3, specifically 2.6, 2.8, 2.9 or 3.

[0041] In the present invention, the early strength agent preferably includes one or more of calcium formate, calcium chloride and sodium sulfate.

[0042] In the present invention, the naphthalene-based water reducer preferably includes one or more of sodium methylene dinaphthalene sulfonate, sodium methyl naphthalene sulfonate and sodium dibutyl naphthalene sulfonate.

[0043] In the present invention, the lithium salt preferably includes lithium sulfate and / or lithium carbonate.

[0044] In the present invention, the particle size of the iron powder is preferably 26-48 μm, specifically 26, 40 or 41 μm.

[0045] In the present invention, the high-efficiency water reducer preferably includes one or more of polycarboxylate water reducer, naphthalene water reducer and aminosulfonate water reducer.

[0046] In the present invention, the role of the anhydrous gypsum is to delay the cement hydration time and improve the early strength, the role of the lime is to provide an alkaline environment and improve workability, the role of the silica fume is to improve the comprehensive performance of the product, promote hydration and accelerate hardening, and improve the early strength of the product, the role of the sodium silicate is to promote coagulation and improve the anti-seepage ability, the role of the naphthalene series water reducer is to reduce the water consumption and improve the fluidity of the material, the role of the early strength agent is to accelerate the cement hydration speed and promote the development of the early strength of the product, the role of the lithium salt is to promote coagulation and improve the early strength, and the cement clinker as the basic raw material of the powder provides the main gelling properties to determine the product The performance and strength of the slag cement are to reduce the hydration heat and improve the later strength. The role of the iron powder is to increase the viscosity and strength and adjust the working performance of the product. The role of the aluminum sulfate is to improve the strength and accelerate the hydration reaction rate. The role of the calcium carbonate is to improve the strength, reduce the volume shrinkage and adjust the setting time. The role of the sodium tripolyphosphate is to improve the particle distribution, improve the uniformity and reduce the water consumption. The role of the water glass is to quickly solidify and enhance the structural strength. The role of the high-efficiency water reducer is to reduce the water consumption and improve the fluidity of the material. The role of the triethanolamine is to promote the hydration process and improve the early strength and durability.

[0047] In a specific embodiment of the present invention, the component A includes the following components in parts by mass: 60 parts of anhydrous gypsum, 20 parts of lime, 10 parts of silica fume, 2 parts of sodium silicate, 0.5 parts of naphthalene-based water reducer, 7 parts of early strength agent, and 0.5 parts of lithium salt;

[0048] The B component includes the following components by mass: 70 parts of cement clinker, 10 parts of slag cement, 10 parts of iron powder, 3 parts of aluminum sulfate, 7 parts of calcium carbonate, and 0.5 parts of sodium tripolyphosphate;

[0049] The C component includes the following components in parts by mass: 25 parts of water glass, 10 parts of emulsion, 50 parts of water, 10 parts of high-efficiency water reducing agent, and 5 parts of triethanolamine.

[0050] In another specific embodiment of the present invention, the component A preferably includes the following components in parts by mass: 80 parts of anhydrous gypsum, 5 parts of lime, 5 parts of silica fume, 5 parts of sodium silicate, 0.7 parts of naphthalene-based water reducer, 4 parts of early strength agent, and 0.3 parts of lithium salt;

[0051] The B component includes the following components by weight: 50 parts of cement clinker, 30 parts of slag cement, 5 parts of iron powder, 4 parts of aluminum sulfate, 10 parts of calcium carbonate, and 1 part of sodium tripolyphosphate;

[0052] The component C comprises the following components in parts by mass: 15 parts of water glass, 20 parts of emulsion, 56 parts of water, 8 parts of high-efficiency water reducing agent, and 1 part of triethanolamine.

[0053] In another specific embodiment of the present invention, the component A includes the following components in parts by mass: 70 parts of anhydrous gypsum, 10 parts of lime, 7 parts of silica fume, 8 parts of sodium silicate, 1 part of naphthalene-based water reducer, 3.2 parts of early strength agent, and 0.8 parts of lithium salt;

[0054] The B component includes the following components by mass: 60 parts of cement clinker, 20 parts of slag cement, 7 parts of iron powder, 8 parts of aluminum sulfate, 5 parts of calcium carbonate, and 0.8 parts of sodium tripolyphosphate;

[0055] The component C comprises the following components in parts by mass: 10 parts of water glass, 20 parts of emulsion, 60 parts of water, 5 parts of high-efficiency water reducing agent, and 5 parts of triethanolamine.

[0056] The present invention has no special limitation on the preparation method of the inorganic environmentally friendly reinforcement material for mining described in the above technical solution, and it can be prepared by a preparation method of a composition well known to those skilled in the art. In a specific embodiment of the present invention, the preparation of the A component and the B component is to use a dry mortar mixer, put each component into the mixer one by one, stir, and then preferably use an automatic packaging machine to package for 5 minutes; the C component is prepared by a stainless steel reactor, put each component into the reactor one by one, stir for 15 minutes, and package.

[0057] The present invention also provides an application of the inorganic environmentally friendly reinforcement material for mining described in the above technical solution, comprising the following steps:

[0058] Mixing component A with part of component C to obtain a first mixed material;

[0059] Mixing component B with the remaining component C to obtain a second mixed material;

[0060] The first mixed material and the second mixed material are injected into the coal rock mass.

[0061] In the present invention, the mass ratio of the part of the C component to the remaining C component is preferably 1:1.

[0062] When in use, pour the component A into mixing tank A, weigh part of the component C, pour it into mixing tank A, and stir evenly; pour the component B into mixing tank B, weigh the remaining component C, pour it into mixing tank B, and stir evenly; connect the mixing tank A and mixing tank B, and inject them into the coal rock mass through a grouting pump to reinforce the surrounding rock.

[0063] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0064] The raw materials used in the present invention are:

[0065] The particle size of sodium silicate is 20-48 μm, the particle size of calcium carbonate is 18-38 μm, the emulsion is styrene acrylic emulsion (solid content is 40%), the naphthalene series water reducer is sodium methylene dinaphthalene sulfonate, the particle size of iron powder is 26-48 μm, the high-efficiency water reducer is polycarboxylic acid water reducer; the modulus of water glass is 3.

[0066] Preparation method:

[0067] The components were mixed.

[0068] Unless otherwise specified in the examples, "parts" are all parts by mass.

[0069] Test standard: AQ / T 1089-2020.

[0070] Example 1

[0071] Component A: 60 parts of anhydrous gypsum, 20 parts of lime, 10 parts of silica fume, 2 parts of sodium silicate, 0.5 parts of naphthalene water reducer, 0.5 parts of lithium sulfate, 7 parts of calcium formate;

[0072] Component B: 70 parts of cement clinker, 10 parts of slag cement, 10 parts of iron powder, 3 parts of aluminum sulfate, 7 parts of calcium carbonate, 0.5 parts of sodium tripolyphosphate;

[0073] Component C: 25 parts of water glass, 10 parts of emulsion, 10 parts of high-efficiency water reducer, 5 parts of triethanolamine, 50 parts of water

[0074] Method of use: weigh 100 parts of component A and pour them into mixing tank A, add 50 parts of component C and stir evenly, weigh another 100 parts of component B and pour them into mixing tank B, add 50 parts of component C and stir evenly, connect mixing tank A and mixing tank B, stir evenly, and inject into the coal rock mass through a grouting pump.

[0075] The use effect of the inorganic environmentally friendly mining reinforcement material of Example 1 was tested, and the results are shown in Table 1.

[0076] Table 1 Test results of inorganic environmentally friendly reinforcement materials for mining in Example 1

[0077]

[0078] Example 2

[0079] Component A includes the following components by mass: 80 parts of anhydrous gypsum, 5 parts of lime, 5 parts of silica fume, 5 parts of sodium silicate, 0.7 parts of naphthalene-based water reducer, 4 parts of calcium formate, and 0.3 parts of lithium sulfate;

[0080] Component B includes the following components by mass: 50 parts of cement clinker, 30 parts of slag cement, 5 parts of iron powder, 4 parts of aluminum sulfate, 10 parts of calcium carbonate, and 1 part of sodium tripolyphosphate;

[0081] Component C includes the following components in parts by mass: 15 parts of water glass, 20 parts of emulsion, 56 parts of water, 8 parts of high-efficiency water reducing agent, and 1 part of triethanolamine.

[0082] Method of use: weigh 100 parts of component A and pour them into mixing tank A, add 50 parts of component C and stir evenly, weigh another 100 parts of component B and pour them into mixing tank B, add 50 parts of component C and stir evenly, connect mixing tank A and mixing tank B, stir evenly, and inject into the coal rock mass through a grouting pump.

[0083] The use effect of the inorganic environmentally friendly mining reinforcement material of Example 2 was tested, and the results are shown in Table 2. The testing method is the same as that of Example 1.

[0084] Table 2 Test results of inorganic environmentally friendly reinforcement materials for mining in Example 2

[0085]

[0086] Example 3

[0087] Component A includes the following components by mass: 70 parts of anhydrous gypsum, 10 parts of lime, 7 parts of silica fume, 8 parts of sodium silicate, 1 part of naphthalene-based water reducer, 3.2 parts of calcium formate, and 0.8 parts of lithium sulfate;

[0088] Component B includes the following components by mass: 60 parts of cement clinker, 20 parts of slag cement, 7 parts of iron powder, 8 parts of aluminum sulfate, 5 parts of calcium carbonate, and 0.8 parts of sodium tripolyphosphate;

[0089] Component C includes the following components in parts by mass: 10 parts of water glass, 20 parts of emulsion, 60 parts of water, 5 parts of high-efficiency water reducing agent, and 5 parts of triethanolamine.

[0090] Method of use: weigh 100 parts of component A and pour them into mixing tank A, add 50 parts of component C and stir evenly, weigh another 100 parts of component B and pour them into mixing tank B, add 50 parts of component C and stir evenly, connect mixing tank A and mixing tank B, stir evenly, and inject into the coal rock mass through a grouting pump.

[0091] The use effect of the inorganic environmentally friendly mining reinforcement material of Example 3 was tested, and the results are shown in Table 3. The testing method is the same as that of Example 1.

[0092] Table 3 Test results of mining inorganic environmentally friendly reinforcement materials of Example 3

[0093]

[0094] Comparative Example 1

[0095] The polyurethane grouting material was directly used for testing. The results are shown in Table 4. The testing method is the same as that in Example 1.

[0096] Table 4 Test results of comparative example 1

[0097]

[0098] Comparative Example 2

[0099] Ordinary cement grouting material (PIII grade grouting) was directly used for testing. The results are shown in Table 5. The testing method is the same as that in Example 1.

[0100] Table 5 Test results of comparative example 2

[0101]

[0102]

[0103] By comparing Tables 1 to 5, it can be seen that the currently used polymer polyurethane grouting material has the characteristics of fast reaction and fast strength, but its flame retardant level is poor, the reaction heat is high, and it is easy to ignite the coal seam; and the ordinary cement grouting material, although the reaction heat is low and the flame retardant level is high, its strength is slow and the reaction is slow, and the effect of "mining after injection" cannot be achieved; the inorganic environmentally friendly reinforcement material for mining of the present invention has the advantages of low reaction heat, high flame retardant level (A-level non-combustible), safe use (no harm to the human body, not easy to cause allergies, etc.), low price, energy saving and emission reduction, etc., and has high construction efficiency, fast reaction speed, and can be quickly cured. The compressive strength is greater than 5MPa in 30 minutes, greater than 10MPa in 1 hour, and greater than 30MPa in 2 hours. After the grouting is completed, coal mining can be carried out.

[0104] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. An inorganic environmentally friendly reinforcement material for mining, characterized in that: Includes independently packaged components A, B and C: The component A comprises the following components by weight: 60-80 parts of anhydrous gypsum, 5-20 parts of lime, 5-10 parts of silica fume, 2-8 parts of sodium silicate, 0.5-1 parts of naphthalene-based water reducer, 3-7 parts of early strength agent, and 0.2-0.8 parts of lithium salt; The B component includes the following components in parts by weight: 50-70 parts of cement clinker, 10-30 parts of slag cement, 5-10 parts of iron powder, 1-8 parts of aluminum sulfate, 5-10 parts of calcium carbonate, and 0.5-1 part of sodium tripolyphosphate; The C component includes the following components in parts by weight: 10 to 25 parts of water glass, 10 to 20 parts of emulsion, 40 to 60 parts of water, 5 to 10 parts of high-efficiency water reducing agent, and 1 to 5 parts of triethanolamine; The mass ratio of component A, component B and component C is 1:1:0.9-1.

2. The inorganic environmentally friendly reinforcement material for mining according to claim 1, characterized in that: The component A comprises the following components by weight: 60 parts of anhydrous gypsum, 20 parts of lime, 10 parts of silica fume, 2 parts of sodium silicate, 0.5 parts of naphthalene-based water reducer, 7 parts of early strength agent, and 0.5 parts of lithium salt; The B component includes the following components by mass: 70 parts of cement clinker, 10 parts of slag cement, 10 parts of iron powder, 3 parts of aluminum sulfate, 7 parts of calcium carbonate, and 0.5 parts of sodium tripolyphosphate; The C component includes the following components in parts by mass: 25 parts of water glass, 10 parts of emulsion, 50 parts of water, 10 parts of high-efficiency water reducing agent, and 5 parts of triethanolamine.

3. The inorganic environmentally friendly reinforcement material for mining according to claim 1, characterized in that: The component A comprises the following components by weight: 80 parts of anhydrous gypsum, 5 parts of lime, 5 parts of silica fume, 5 parts of sodium silicate, 0.7 parts of naphthalene-based water reducer, 4 parts of early strength agent, and 0.3 parts of lithium salt; The B component includes the following components by weight: 50 parts of cement clinker, 30 parts of slag cement, 5 parts of iron powder, 4 parts of aluminum sulfate, 10 parts of calcium carbonate, and 1 part of sodium tripolyphosphate; The component C comprises the following components in parts by mass: 15 parts of water glass, 20 parts of emulsion, 56 parts of water, 8 parts of high-efficiency water reducing agent, and 1 part of triethanolamine.

4. The inorganic environmentally friendly reinforcement material for mining according to claim 1, characterized in that: The component A comprises the following components by weight: 70 parts of anhydrous gypsum, 10 parts of lime, 7 parts of silica fume, 8 parts of sodium silicate, 1 part of naphthalene-based water reducer, 3.2 parts of early strength agent, and 0.8 parts of lithium salt; The B component includes the following components by mass: 60 parts of cement clinker, 20 parts of slag cement, 7 parts of iron powder, 8 parts of aluminum sulfate, 5 parts of calcium carbonate, and 0.8 parts of sodium tripolyphosphate; The component C comprises the following components in parts by mass: 10 parts of water glass, 20 parts of emulsion, 60 parts of water, 5 parts of high-efficiency water reducing agent, and 5 parts of triethanolamine.

5. The inorganic environmentally friendly reinforcement material for mining according to any one of claims 1 to 4, characterized in that: The particle size of the sodium silicate is 20 to 48 μm.

6. The inorganic environmentally friendly reinforcement material for mining according to any one of claims 1 to 4, characterized in that: The particle size of the calcium carbonate is 18 to 38 μm.

7. The inorganic environmentally friendly reinforcement material for mining according to any one of claims 1 to 4, characterized in that: The emulsion includes one or more of styrene-acrylic emulsion, pure acrylic emulsion and water-based polyurethane emulsion.

8. The inorganic environmentally friendly reinforcement material for mining according to any one of claims 1 to 4, characterized in that: The modulus of the water glass is 2.6 to 3.

3.

9. The inorganic environmentally friendly reinforcement material for mining according to any one of claims 1 to 4, characterized in that: The early strength agent includes one or more of calcium formate, calcium chloride and sodium sulfate.

10. The use of the inorganic environmentally friendly reinforcement material for mining according to any one of claims 1 to 9, characterized in that: The following steps are involved: Mixing component A with part of component C to obtain a first mixed material; Mixing component B with the remaining component C to obtain a second mixed material; The first mixed material and the second mixed material are injected into the coal rock mass.

Citation Information

Cited By

  • Mining high-viscosity consolidation material and preparation method thereof

    CN119912230A

  • A high-viscosity consolidation material for mine use and its preparation method

    CN119912230B

  • Mining inorganic reinforcing material and preparation method thereof

    CN122608369A

  • A mine inorganic reinforcing material and its preparation method

    CN122608369B